DAMPAK HUTAN KEMASYARAKATAN TERHADAP ASPEK EKONOMI MASYARAKAT DESA SEI. NAGALAWAN KABUPATEN SERDANG BEDAGAI - Ahmad Guru Hasibuan; Citra Rahmatia; Riko Kurniawan (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2026)
Indonesia is a tropical country that has quite extensive forest areas. The existence of this forest area is a national asset that must be managed and developed in a better direction, so that it can be used sustainably. The existence of Minister of Environment and Forestry Regulation Number P.83/Menlhk/Kum.1/10/2016 concerning Social Forestry is of course an opportunity for the people of Sei Nagalawan Village to participate in this program. The aim of this research is to determine the effect of social forestry permits on improving the economy of the Muara Baimbai Mangrove Conservation Group. The research method used is a qualitative method. The data collection carried out during the research was carried out using data triangulation, namely a data collection technique that combines various data collection techniques and existing data sources and constraints in the management of the Muara Baimbai Mangrove Conservation Group's HKm. Based on the research results, it can be concluded that social forestry permits have an effect on improving the economy of the Muara Baimbai Mangrove Conservation Group during 2020-2024, experiencing a decrease in visitors. External and internal factors are obstacles faced in managing the Community Forest of the Muara Baimbai Mangrove Conservation Group.